Pemodelan 3D Jembatan Lengkung, Studi Kasus Jembatan Bukit Sulap, Menggunakan Software Autodesk Revit - Kharimah, Muhammad Ihsanul; Hidayat, Benny (Universitas Andalas, 2023)
Infrastructure is an essential sector in a country, and infrastructure development reflects the country's progress. Infrastructure development is a priority, but the implementation of infrastructure projects needs to pay attention to time, costs and quality. Building Information Modeling (BIM) has the potential to minimize errors and increase efficiency. BIM is a method that was originally applied to the AEC (Architecture, Engineering and Construction) industry. BIM technology makes it possible to create 3D building models that contain information, analysis of work volume calculations, scheduling, and cost calculations. There is several software that applies BIM technology such as Autodesk Revit, Autodesk Advanced Steel, Tekla Structures and Navisworks. BIM technology has been widely applied in construction projects in Indonesia, be it buildings, roads or bridges. In this research, modelling of a steel truss bridge with an arch type was carried out using Autodesk Revit software. This research was conducted to determine the capabilities and limitations of Autodesk Revit software in modelling arch-type steel frame bridge structures. The modelling in this research uses DED (Detailed Engineering Design) image sources for the Bukit Sulap Bridge project, which were obtained from the PUPR Department of Lubuklinggau City. The modelling carried out is in the form of steel frames, bracing, girder beams and bridge connections.